IEEE MTT-S International Microwave Symposium Digest, 2003
DOI: 10.1109/mwsym.2003.1212474
|View full text |Cite
|
Sign up to set email alerts
|

A 19 GHz low phase noise HFET VCO MMIC

Abstract: A 19 GHz extremely low phase noise voltage controlled oscillator (VCO) MMIC is presented. To reduce the phase noise of the VCO, a hetemstructure field effect transistor (HFET) is used as the active device, because its property of low frequency noise is superior to that of high electron mobility transistor (HEMT). This VCO showed the typical phase noise of -120 dBdHz at 1 MHz offset from carrier. This performance is better than other VCOs operating above 10 GHz. Measured tuning range is 400 MHz and output power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…www.TheOncologist.com ©AlphaMed Press 2013 CME Gy of local radiotherapy and concluding with a further five cycles of CHOP chemotherapy [70]. Since then, these findings have been supported by a systematic review performed by Doria et al, who found recurrence rates of a 7.7% following chemoradiation therapy, 37.1% following radiotherapy alone, and 43% following chemotherapy alone [79].…”
Section: Combined Chemoradiotherapymentioning
confidence: 88%
See 2 more Smart Citations
“…www.TheOncologist.com ©AlphaMed Press 2013 CME Gy of local radiotherapy and concluding with a further five cycles of CHOP chemotherapy [70]. Since then, these findings have been supported by a systematic review performed by Doria et al, who found recurrence rates of a 7.7% following chemoradiation therapy, 37.1% following radiotherapy alone, and 43% following chemotherapy alone [79].…”
Section: Combined Chemoradiotherapymentioning
confidence: 88%
“…In contrast, Cha et al showed in their study of 23 patients that 63% of those diagnosed after 1993 (n ϭ 11) were diagnosed with FNAC alone and thus did not require an open biopsy [55]. An older paper by Matsuzuka et al contradicts this by stating that an open biopsy is required for subtyping of disease despite the fact that a diagnosis was reached in 79% of patients with FNAC [70].…”
Section: Surgical Open Biopsymentioning
confidence: 98%
See 1 more Smart Citation